2011
DOI: 10.1111/j.1467-7660.2011.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

The Micropolitics of Indigenous Environmental Movements in the Philippines

Abstract: Indigenous movements face what Stuart Kirsch has called the ‘risks of counterglobalization’, which can distort their objectives into an all‐or‐nothing position with respect to development. In this contribution, I explore a case from the Philippines, where a movement originally conceived in terms of indigenous rights grew to include a more diverse mix of constituents and claims. This trajectory has made the movement vulnerable to charges of inauthenticity, particularly since the corporation it opposes has spons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Just as self-identification draws on different aspects of indigeneity across regions, there is also variance in the extent of alliances between Indigenous and non-Indigenous CSOs. This could be due to the fact that Indigenous and non-Indigenous CSOs have different understandings of Indigenous values and symbolism (Kirsch 2007;Theriault 2011). For example, the Indigenous movement against the Ok Tedi mine in Papua New Guinea drew criticism from non-Indigenous organizations for simultaneously attempting to protect the environment while also engaging in development and financial opportunities seen as contributing to negative externalities (Kirsch 2007).…”
Section: Different Experiences Understandings and Expectationsmentioning
confidence: 99%
“…Just as self-identification draws on different aspects of indigeneity across regions, there is also variance in the extent of alliances between Indigenous and non-Indigenous CSOs. This could be due to the fact that Indigenous and non-Indigenous CSOs have different understandings of Indigenous values and symbolism (Kirsch 2007;Theriault 2011). For example, the Indigenous movement against the Ok Tedi mine in Papua New Guinea drew criticism from non-Indigenous organizations for simultaneously attempting to protect the environment while also engaging in development and financial opportunities seen as contributing to negative externalities (Kirsch 2007).…”
Section: Different Experiences Understandings and Expectationsmentioning
confidence: 99%
“…Relations of sovereignty are often dominated by state and capital interests, but a wide range of other actors are also part of that relationship and can exert more power within it over time. Thus, a relational approach to sovereignty can link more traditional debates about globalization and state sovereignty with those of peasant-oriented food and land sovereignty (Altieri and Toledo, 2011;Borras and Franco, 2012;Wolford et al, 2013) or the sovereignty of indigenous peoples over their territories (Theriault, 2011). These debates are concerned with appropriating sovereignty relationships towards the interests of the marginalised, oppressed and exploited.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Recently, scholars have argued that the ‘expulsion‐resistance scenario’ is often assumed rather than demonstrated (Borras and Franco, ). Several careful ethnographic studies have shown that the link between land acquisition, displacement and resistance is not straightforward, and that local political reactions to forced acquisition of land are varied and complex (Baviskar, ; Borras and Franco, ; Chakravorty, ; Dao, ; Dwivedi, ; Hall et al., ; Milgroom, ; Nielsen, ; Nilsen, ; Oliver‐Smith, ; Oskarsson and Nielsen, ; Theriault, ; Venkateswaran, ). Moreover, resistance may not be the only response to dispossession.…”
Section: Introductionmentioning
confidence: 99%